Gopāla Bhām̐ḏa - Caṭṭopādhyāẏa, Hariśacandra (Saumya Prakāśana, 2023)
Humorous stories on Gopāla Bhān̐ṛa, court jester in medieval Bengal, India.
Humorous stories
Keywords: Gopāla Bhān̐ṛa; Fiction.; Humorous stories; Bengali.